NEW FORMS OF MENTAL EXPRESSION THROUGH NEOLOGISMS (Eureka Journal of Language, Culture & Social Change, 2026)
In this article, the scientific views and opinions of scientists on new forms of mental expression by means of neologisms are presented, and neologisms in French and Uzbek languages are analyzed. Neologisms that appeared in the two unrelated languages mainly in the last 5-6 years were analyzed. Psycholinguistically, neologisms are shown as attention-grabbing units with emotional impact, scientifically proven in several tables and diagrams.
Keywords: Emotional impact, attention, human psyche, psycholinguistics, neologism, social network, artificial intelligence, password, link, body camera, social phenomenon, social sphere, cultural sphere, scientific and technical sphere, remote work, digitization, human thinking, psychological changes.